Expanding the knowledge of Brazilian Gastrotrich biodiversity: Freshwater Paucitubulatina (Gastrotricha: Chaetonotida) from Northeastern Brazil - Axell Kou Minowa; André Rinaldo Senna Garraffoni (Zoologia (Curitiba))
ABSTRACT Knowledge of neotropical freshwater gastrotrichs, especially in Brazil, has gained momentum in the past decades, with new species being discovered yearly, accumulating in the last 30 years more than 10% of known species worldwide. Nevertheless, there is still much to accomplish in the field, with large geographical gaps to be filled, especially in continental countries such as Brazil. In the present study, we report the partial results of an expedition that, for the first time, sampled the inland waters of Alagoas, Bahía, and Pernambuco states, Northeast Region, Brazil, and found ten species belonging to five genera of Chaetonotidae. We report the first occurrence in Brazil of Chaetonotus majestuosus Grosso & Drahg, 1984, originally described from Argentina, and the second record in Brazil of Chaetonotus dadayi Schwank, 1990, originally found in Paraguay, and the first occurrence beyond ‘terra typica’ of Heterolepidodermella jureiense Kisielewski, 1991, originally discovered in Southeastern Brazil. Furthermore, we report members of species in conformity to species originally described in European countries Chaetonotus cf. persetosus Zelinka, 1889, and Chaetonotus cf. oculifer Kisielewski, 1981, although further investigations are needed to confirm the occurrence of such widespread lineages. Finally, we list three putative undescribed species related to Lepidochaetus aff. zelinkai (Grünspan, 1908), Chaetonotus aff. hoanicus Schwank, 1990 and Chaetonotus aff. acanthocephalus Valkanov, 1937. This new survey increases the list of northeast Brazilian freshwater gastrotrichs to 13 species.